The own-race bias for face recognition in a multiracial country - Wong, Hoo Keat (2020)
The own-race bias (ORB) is a well-documented phenomenon whereby people are more accurate at recognising faces from their own-race group compared to faces from different race groups (Meissner & Brigham, 2001). While empirical studies have reported the robustness of the ORB across racial groups, the finding that the ORB is negatively related to exposure to other-race individuals suggests that may not necessarily apply to individuals who were born and have lived in a multiracial society. This thesis fills a gap in the ORB literature by examining the role of multiracial immersion experience as well as potential perceptual/attentional mechanisms in modulating the ORB by employing a series of face memory and face perceptual tasks on different racial groups (i.e. Malaysian-Malay, Malaysian-Chinese, Malaysian-Indian, African and Western-Caucasian individuals).